NEW CHALLENGES FOR MARINE ENVIRONMENTAL PROTECTION LAWS OF VIETNAM: APPROVE FULL MARPOL CONVENTION 73/78 - Tan, Pham Van (PEOPLE: International Journal of Social Sciences, 2015)
Is a coastal country, with the natural characteristics, geographic location, Vietnam maritime operations have favorable conditions development for the purposes of trade, tourism, services, exploration and exploitation of natural resources and geodetic survey..., bring a lot of value to the development of the country. However, with the development of the maritime, the Vietnam sea is facing marine pollution by maritime operations, the marine resources are diminished. Although there are many solutions but the real effect is not high. Law on pollution control in the marine operations is limited. Maritime law of 2005 only has 4 rules stipulate the prevention of environmental pollution. Environmental Protection law of 2005 only stipulates principle of the protection of the marine environment in general. Management state system of control marine pollution in Vietnam has many shortcomings. So, the signing, approving and implementing the treaties, international laws on maritime as well as apply appropriate international maritime law system has an important role in completing the laws system on protection of the marine environment of Vietnam in maritime operations. Within the scope of this paper, mainly refers to the need to modify the Law on the protection of the marine environment in Vietnam to ready for approving fully MARPOL Convention 73/78.